Saneamento Ambiental: participação popular e transversalidade em matéria de políticas públicas - Gil, Gustavo Luz (2010)
The present paper aimed at analyzing the public policies of environmental sanitation under the scope of popular participation and transversality. Both the Brazilian legislation and the contemporary doctrine highlight the need and significance of the popular participation and of the articulation of the public policies regarding the environmental sanitation, this happens because such policies are conditioning to the greater juridical good protected by Law, be whatever life it is and, a quality life. One understands that the environmental sanitation does not limit itself to the aspects of the basic sanitation, established by the Federal Law n. 11.445/2007, which, despite contemplating most of the actions in sanitation is not restricted to it, given that the environmental sanitation also involves the environmental education, the vectors control, housing, and all the other social aspects related to the sanitation of the environment. In fact, the issue of the environmental sanitation is intrinsically related to the sectors policies of basic sanitation, health, environment, hydric resources, solid residues as well as the urban policy. It is needed, therefore, to carry out an analysis of these policies under the point of view of the social rights as they are linked to the duty of the State, facing a historical look of the very evolution of the State role itself. In this context, one might highlight that the democratization of the public space shows itself, nowadays, as a demand of the plural society which searches for, from the local reality, an improvement in quality of life. And, citizenship comes to be seen in its broader concept, coming to be, as well, conceived as an environmental citizenship, convergent in terms of environmental sanitation. The present research was an exploratory description, once it was developed with the use of theoretical sources, which enabled the reading of the juridical norms and doctrine about public policies and its interface regarding the environmental sanitation, at the same time a study about the present public policy of environmental sanitation of Manaus was carried out, the “Programa Social e Ambiental dos Igarapés de Manaus – PROSAMIM” (Social and Environmental Program of the Streams in Manaus), being implemented since 2003 by the State Government. Aiming at verifying the issue of democratization of the public space, a field research was performed along with one of the housing units of the Program, the Manaus Residential Park – PRM, interviewing 150 residents, with the main objective of investigating if there was a dialogue between the Government and the community when implementing, carrying out and concluding the work of PROSAMIM. The field research data revealed that, according to the population of PRM, there were many meetings to discuss the project; however, it was possible to notice that this discussion was attained, in most of the cases, only to the informational aspect of the Program, being the consultation and voting characters disregarded. Besides, attention is drawn to the fact that 82% of the interviewees ranked PROSAMIM-PRM as good or excellent. Such data reveal that, at least, the population of PRM who stayed on site – excluding, therefore the part of the population who moved – legitimate the referred public policy of environmental sanitation. It is true that in terms of control of the public policies, the role of the Judiciary is still showed as fundamental, notoriously when the Public Power omits itself. In general, it was observed that there is a need of a greater political commitment towards the department of environmental sanitation, thus this id the only way that a full guarantee will be granted in a Democratic Law State, the right to citizenship and humane dignity, therefore, making the terms of the Federal Republic of Brazil true.